Pogled diplomiranega inženirja ortotike in protetike na Mednarodno klasifikacijo funkcioniranja, zmanjšane zmožnosti in zdravja (MKF) - Mlakar, Maja (Rehabilitacija (Ljubljana), 2012)
Background: Certified prosthetists and orthotists (CPOs) need various pieces of information about persons for whom they produce a prosthesis or an orthosis in order to produce a functional device that will meet the users needs. In every-day practice we face many difficulties with transfer of information acquired during medical examination, which is or is not recorded in the medical documentation. Introducing the International Classification of Functioning, Disability and Health (ICF) as an obligatory part of medical documentation would convey more information about the health and the functional status of the patient. The aim of our study was to find out if CPOs read medical documentation and if they are familiar with the ICF. We also wanted to find out their opinions about usefulness of medical documentation without and with the ICF. Methods: All CPOs who work in clinical practice in Slovenia were invited to participate in the study. An example of medical documentation with ICF was introduced to them, which served as the basis to conduct a structured interview. Results: Fifteen CPOs participated. Half of them read the medical documentation every time before they start to work on a case. The same proportion of the group considers medical documentation as useful for their work. The highest scores for usefulness of medical documentation were given from the CPOs working in the field of orthotics, and the lowest scores by those working in lower limb prosthetics. Medical documentation with ICF was mostly assessed as more or equally useful as medical documentation without ICF. Eleven CPOs met the ICF for the first time in this study. Conclusion: We believe that it would be useful to supplement medical documentation with relevant ICF categories, so that more information would be transmitted to the CPO about the health and the functional status of the patient.
Keywords: classification; Disabled persons; International classification of diseases; klasifikacija; mednarodna klasifikacija bolezni; ortotika; osebe z zmanjšanimi zmožnostmi; protetika